Akkaraman koçların serum testosteron düzeylerinde ve spermatogenesisindeki mevsime bağlı değişikliklerin araştırılması. II. Seminifer tubul çapları ve spermatogenesisdeki değişimler (Investigation of Seasonal Changes in Serum Testosterone Levels and Spermatogenesis in Akkaraman Rams. II. Variations in Diameters of Seminiferous Tubule and Spermatogenesis) - Türk, G; Demirci, E (My University, 2005)
This study was conducted to investigate the seasonal variations in diameters of seminiferous tubul and spermatogenesis in Akkaraman rams. In this investigation, 120 Akkaraman rams, which were brought to the slaughterhouse for slaughtering and whose ages ranged between 14-18 months, were used. Tissue samples were taken from testes and cauda epididymides. Histological trimes were prepared in these tissues and examined. Diameters of seminiferous tubule were measured by the ocular micrometer. While the highest annual value of diameters of seminiferous tubule were found as 211.80±2.19 ?m in October. The lowest value of this parameter was determined as 132.30±1.59 ?m in February. Diameters of seminiferous tubule reached their maximum levels in autumn and minimum levels in winter. Variations of this parameter among months, and seasons were statistically significant (p<0.05). Spermatogenesis maintained throughout the year, being the most effective in autumn, but some variations were seen in the structure of testis between autumn and the other seasons. Both mitotic and meiotic divisions increased in autumn compared to the spring, summer and winter. Spermatogonia, primary and secondary spermatocytes, round and elongated spermatids began to increase in mid-August, full increased their maximum sizes during September-November and began to decline in December. Sertoli and Leydig cell concentrations were unaffected by the seasonal changes. Spermatozoa concentration in the cauda epididymides was affected by the seasonal variations and it increased during autumn. In conclusion, diameters of seminiferous tubule and the cells of spermatogenesis in Akkaraman rams were affected significantly by month and seasonal alterations and these features had a positive effect on fertility and showed the most improvement especially in autumn, the breeding season is for rams.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Koç Seminifer Tubul Çapı Spermatogenesis Mevsim (Ram Diameter of Seminiferous Tubule Spermatogenesis Season)